ANALYSIS OF WASTEWATER AERATION METHODS IN AERATION TANKS - Murtazayev F.A.; Mirzayev M. (Journal of new century innovations, 2022)
Annotation: The quality of biological purification largely depends on the operation of aeration systems. This article presents an analysis of the search for the most economical and effective variant of wastewater aeration methods in aeration tanks, provides brief characteristics and conditions of use, and discusses the advantages and disadvantages of mechanical, pneumatic and jet aerators.